Isykâliyyât at-Ta’rîf bi an-Nazhariyyah al-Lisâniyyah ‘an Tharîq at-Tarjamah - Murtadha Yusuf (Jurnal Internasional Pendidikan Bahasa Arab, 2022)
This study focuses on one major aspect of the Arabs' adaptation of Text Linguistics Theory among many Modern Linguistic Theories that scholars have been inspired by and whose efforts have manifested into publications, books and translations. However, It has been discovered that these efforts vary in description to theory’s direction, perception, and pluralizes concept and terminology. This is occasioned by analytical definitions that defined its datum, as well as methodological foundations that scholars depended on for reception. This study therefore, looks into defining text linguistics through translation, and related issues like terminology chaos and language mixture between the transmitter and the transmitted. However, it also analyzes methodological mechanism in order to establish boundary between the thought of Western textual linguistics and Arabic system which differs somewhat from modern discussion.